Moodle-Based Flipped Learning-Model to Increase Basic Translation Skills and 21st Century Skills - Andri Purwanto; Yumna Rasyid; Miftahulkhairah Anwar; Ilza Mayuni (Scope : Journal of English Language Teaching, 2022)
Developing Moodle-based flipped learning model and integrating it with collaborative i-tool SmartCAT is one of the greatest challenges in Translation courses. Product validation is carried out by translation, Flipped Learning, instructional design and Learning Management System experts. To obtain expert consensus regarding the validity of the developed hypothetical model, the Delphi technique is used, namely the conclusion of the results of various expert opinions that are collected, searched for points of similarity, and summarized so that it becomes a common consensus. The consensus of experts includes the following aspects: 1) identification of problems through needs analysis, 2) priority determination, namely determining the type and manufacture of the product, 3) determining program objectives, and 4) determining solutions to solve problems. The next stage is to try it out on 10 lecturers and 60 students in the Translation course in the English Education Study Program. This trial was used to determine the impact of Flipped Learning and the subject’s perception of the application of the product in a lecture activity. The conclusion of the consensus results of the validity of the experts and the perception of the subject in this study were analyzed by the percentage method, while the determination of the impact of learning with the average difference test of the subject’s value. This research is expected to have a positive impact on Moodle-based Flipped Learning through the developed product, which can significantly improve students’ Basic Translation Skills and Twenty-First Century Skills.